Modelo para o estímulo à criação de spin-offs acadêmicas baseado em ecossistemas empreendedores - Oliveira, Meire Ramalho de (2015)
This paper presents a model which aims to stimulate the creation of academic spin-offs by Brazilian Scientific and Technological Institutions (STI), based on experiences of the University of Georgia, University of California, Polytechnic University of Valencia and University of Porto - institutions with high rates of business creation and environment articulate entrepreneur. This model consists of a set of actions or activities that aim to strengthen the entrepreneurial ecosystem. The research that led to the model took place in six stages: Characterization of North American Universities (Phase I); Ecosystem Analysis Entrepreneurs (Phase II); Research (Phase III); Development Model to Business Creation (Stage IV); Model Validation by Expert Panel (Stage V) and Settings (Stage VI). The first version of the model was based on the Babson Entrepreneurship Ecosystem Project, stimulus bill entrepreneurship, developed by Daniel Isenberg. The project unfolded in a model that shows that an environment to encourage entrepreneurship is not made up of only one element, but by a group of structures that working together strengthen this ecosystem. The initial model constructed by this research we used the six elements specified by Isenberg, namely: policies, financial resources, culture, supporting institutions, human capital and markets. The first version of the created model was then validated by the Expert Panel for Technical. The second version of the model, now validated - Model for Spin-offs Creation of Academic Based on Ecosystem Entrepreneurs - consists of three basic elements: the institutional arrangements, policies and entrepreneurial culture. The institutional arrangements are formed by agencies that facilitate technology development, the Technology Transfer Office (TTO), the Center for Entrepreneurship (CE), the Business School (BS), the Incubators and Science Parks (I / SP), the Junior Enterprise (EJ) and Entrepreneurs Network (RE). In addition to the institutional arrangements, the model is composed of other permeable layers, which are the policies that regulate the actions in this ecosystem and the entrepreneurial culture that disseminates the concept within the institution. Permeable layers are justified because they represent a border that information, knowledge and financial resources circulate between these elements that make up the entrepreneurial ecosystem and the external environment. And in that ecosystem also move new ventures. The model provides guidance in three of STI ripening stages: initial, intermediate and mature. The first STI fits into one of these stages and then uses the appropriate guidance to its stage.